Examination of birthplace and birthdate in world junior ice hockey players - Bruner, M. W.; Macdonald, D. J.; Pickett, W.; Côté, J. (Journal of Sports Sciences, 2011)
The present study investigated birthdate (known as the Relative Age Effect; RAE) and birthplace as determinants of expertise in an international sample of elite ice hockey players. The sample included 566 World Junior (WJR) ice hockey players from four countries (Canada, n = 153; USA, n = 136; Sweden, n = 140; Finland, n = 137). Participants competed in the International Ice Hockey Federation World U20 Championship between 2001 and 2009. A series of Poisson regression models were conducted to examine the consistency of direct then interactive relationships between both birthdate and birthplace and WJR membership across the four countries (Canada, USA, Sweden, and Finland). Findings revealed a consistent RAE across the four countries for World Junior participation from 2000 to 2009. WJR players from the four countries were also less likely to be from major cities. In addition, there was no evidence in any of the four countries of an interaction between RAE and birthplace. Future research should explore the contextual and cultural factors that influence elite athlete development in smaller towns, cities and communities.